Poverty Occurrency Probability on Oil Palm Farmer Households - Nyayu Neti Arianti; Muhamad Harismanto; Agus Purwoko (Badan Penerbitan Fakultas Pertanian (BPFP), 2018)
The research was aimed at analyzing poverty level of non-plasma oil palm farmer households and determining factors that influence their poverty occurrence probability. This research was conducted by surveying ninety non-plasma oil palm farmer households in Mukomuko District. The poverty level was quantified method by comparing household income with the World Bank poverty line, i.e. US 2/capita/day. Households were categorized into poor if their income is less than US 2/capita/day or Rp 26,908.00/capita/day (with an exchange rate of Rp 13,454.00 per US ), vice versa. To determine factors affecting the probability of poverty occurrence, the binary logistic model was applied. The results showed that the average non-plasma farmer household income was Rp 39,484.00/capita/day. With the level of exchange rate applied in this research, it was found that forty percent households were below the poverty line. Land variable negative and significantly affects the probability of poverty occurrence while the family size was positive significant. Other factors including education, age, and the existence of other jobs had an insignificant effect.Keywords: probability, poverty, oil palm, household